2022
DOI: 10.1097/prs.0000000000009820
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Public Perceptions, Attitudes, and Concerns About Breast Implants and Their Complications: A National Survey with Implications for Practice

Abstract: esthetic and reconstructive implant-based breast operations are among the most common plastic surgery procedures. Breast augmentation has ranked as the top cosmetic procedure since 2006, and a combined total of more than 380,000 implant-based procedures are performed annually in the United States. 1,2 Despite the continuous popularity of these procedures, short-and long-term complications such as capsular contracture and implant migration are not uncommon. [3][4][5] Approximately 25% to 36% of women experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…They continue to be one of the most common surgical procedures, with over 380 000 breast implant-related operations being performed every year. 25 Large studies in the 1990s showed that both silicone and saline breast implants were safe and did not increase the risk of malignancy. 26 In the early 2000s, clinicians started reporting on anaplastic large cell lymphomas (ALCL) arising within the implant capsule pocket.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They continue to be one of the most common surgical procedures, with over 380 000 breast implant-related operations being performed every year. 25 Large studies in the 1990s showed that both silicone and saline breast implants were safe and did not increase the risk of malignancy. 26 In the early 2000s, clinicians started reporting on anaplastic large cell lymphomas (ALCL) arising within the implant capsule pocket.…”
Section: Discussionmentioning
confidence: 99%
“…Breast implants have been widely used for aesthetic and reconstructive purposes since the 1970s in the United States. They continue to be one of the most common surgical procedures, with over 380 000 breast implant‐related operations being performed every year 25 . Large studies in the 1990s showed that both silicone and saline breast implants were safe and did not increase the risk of malignancy 26 …”
Section: Discussionmentioning
confidence: 99%
“…Fears surrounding implant-based reconstruction were largely based on widely held popular misconceptions rather than evidence-based information. (30,31) Women described disapproval of synthetic or foreign materials and fears of the potential effects of these materials on complications or increased risk of cancer recurrence. While no data surrounding cultural preferences in regard to reconstructive modalities currently exists, a national cohort of 92, 960 women from 2005-2014 demonstrated that NA/AI women were more likely to receive autologous reconstruction.…”
Section: Discussionmentioning
confidence: 99%